- 1-214-256-5804
- info@tutorpace.com

First convert the given mixed fractions to improper fractions.

This implies: 6 2/3 = [(3 * 6) + 2]/ 3 = 20/3.

Similarly, 4 1/3 = [(3 * 4) + 1]/ 3 = 13/3.

Subtract the above two improper fractions: 20/3 – 13/3 = (20 – 13)/ 3 = 7/3.

Now converting 7/3 to mixed fraction, we do the long division which gives quotient as ‘2’ and remainder as ‘1’==> 2 1/3.

Therefore, 6 2/3 – 41/3 = 2 1/3.

First convert the given mixed fractions to improper fractions.

This implies: 2 4/5 = [(5 * 2) + 4]/ 5 = 14/5.

Similarly, 1 3/5 = [(5 * 1) + 3]/ 5 = 8/5.

Subtract the above two improper fractions: 14/5 – 8/5 = (14 – 8)/ 5 = 6/5.

Now converting 6/5 to mixed fraction, we do the long division which gives quotient as ‘1’ and remainder as ‘1’==> 1 1/5.

Therefore, 2 4/5 – 1 3/5 = 1 1/5.